Adaptation of the Children and Adolescents Psychological Distress Scale to Azerbaijani: Exploring its Relationship with Psychological Distress, Wellbeing, and Life Satisfaction - Aliyev, Bakhtiyar; Rustamov, Elnur; Nahmatova, Ulviyya; Aliyeva, Matanat; Rustamova, Narinj; Asadov, Fuad; Zalova Nuriyeva , Ulkar (Journal of Education Culture and Society, 2025)
Aim. In recent years, the concept of psychological distress among children and adolescents has emerged as a novel focal point in mental health research, garnering significant scholarly attention. This paper presents an investigation into the Children and Adolescents Psychological Distress Scale (CAPDS), including its adaptation to the Azerbaijani language. Methods. Data was collected from 2217 adolescents for the adaptation study. During the adaptation process, confirmatory factor analysis, item response theory, network analysis, reliability coefficients, and predictive validity were examined. Results. We validated the 10-item version of the CAPDS through confirmatory factor analysis. Item Response Analysis further demonstrated the robust discriminative capabilities of all scale items. Various reliability coefficients affirmed the commendable internal consistency of the CAPDS. The study also encompassed correlation and network analyses, shedding light on the intricate associations between CAPDS and key variables, including depression, anxiety, stress, mental well-being, and life satisfaction. Finally, an examination was conducted to assess whether the CAPDS could predict psychological distress, mental well-being, life satisfaction, and certain demographic variables. Conclusion. This comprehensive inquiry into psychological distress among children and adolescents elucidates its profound individual and societal implications, providing valuable insights into a phenomenon that has become increasingly relevant in the contemporary social and educational landscape.